The Impact of Strategic Drift and Tactical Wear – Out: An Anecdote Example: The Case of the Distribution of Petroleum Products by Nigeria National Petroleum Corporation (NNPC) - Gajere, Monica (International Journal of Emerging Trends in Social Sciences, 2018)
The focus of this paper is to give an anecdote example of the impact of strategic drift and tactical wear – out using the case of the distribution of petroleum products by Nigeria National Petroleum Corporation (NNPC). Based on industry internal documentation, market reports, and the experience of the populace, the reasons for NNPCS strategic drift and tactical wear - out are based on its current and historical strategies and tactics. The current practices have become obsolete because customer needs, human resource needs, technology, and the environment (political, social and economic factors) change the rules of the game and these had impacts on NNPC’s business activities. As a result, strategies and tactics have become tired or worn-out. The paper suggests that NNPC re-addressed its current strategies in line with the current environmental factors to avoid drift situations by exploring new opportunities and exploiting existing ones to avoid strategic drifts. Also the paper suggests that NNPC could chose between adaptation and evolution or reconstruction and revolution as a change in the marketing strategy depending on the degree of the strategic drift or wear out.